Reframing Gendered Roles through Maṣlaḥah in Islamic Family Law - Diah Siti Sa`diah; Christopher Michael Cason; Idzam Fautanu; Dudi Abdul Hadi (Madania: Jurnal Kajian Keislaman, 2025)
This article explores how married Muslim women navigate the boundaries of gendered roles, as they combine professional careers and religious activism, and the implications of this negotiation about family welfare in contemporary Islamic law. Using a normative empirical methodology, it is an amalgamation of doctrine analysis of Islamic legal norms and field data on concrete career women practicing as activists in Islamic organizations in West Java, Indonesia. The conceptual framework is guided by Muhammad Shahrur’s Limit Theory (hadd al-adnâ and hadd al-a‘lâ) pursued alongside maqâṣid al-syarîʿah in order to determine demarcations between domestic duties as against public participation. To evaluate the substantive impact of women’s dual roles on family well-being, this study develops a maslahah-Based Family Welfare Index, incorporating core maqâṣid domains religion, life, intellect, progeny, and wealth alongside psychosocial indicators. The findings reveal that women’s participation in public and religious spheres does not inherently undermine Islamic family norms when conducted within flexible yet principled limits. Instead, optimal family welfare emerges when role negotiation is supported by spousal cooperation, institutional flexibility, and contextual legal interpretation. This study contributes to contemporary Islamic legal discourse by offering a measurable framework for assessing gendered role balance and by proposing a normative model that reconciles Islamic legal principles with evolving gender realities. It advances Islamic family law beyond rigid dichotomies by foregrounding substantive justice and contextual maslahah as central evaluative standards. Artikel ini mengeksplorasi bagaimana wanita Muslim yang sudah menikah menavigasi batas-batas peran gender, saat mereka menggabungkan karir profesional dan aktivisme agama, dan implikasi dari negosiasi tentang kesejahteraan keluarga dalam hukum Islam kontemporer. Dengan menggunakan metodologi empiris normatif, ini merupakan penggabungan analisis doktrin norma hukum Islam dan data lapangan tentang perempuan karir konkret yang berpraktik sebagai aktivis di organisasi Islam di Jawa Barat, Indonesia. Kerangka konseptual dipandu oleh Teori Batas Muhammad Shahrur (hadd al-adnâ dan hadd al-a'lâ) yang dikejar bersama maqâṣid al-syarîʿah untuk menentukan demarkasi antara tugas domestik terhadap partisipasi publik. Untuk mengevaluasi dampak substantif dari peran ganda perempuan terhadap kesejahteraan keluarga, penelitian ini mengembangkan Indeks Kesejahteraan Keluarga Berbasis maslahah, yang menggabungkan domain maqâṣid inti  agama, kehidupan, kecerdasan, keturunan, dan kekayaan di samping indikator psikososial. Temuan ini mengungkapkan bahwa partisipasi perempuan dalam bidang publik dan agama tidak secara inheren merusak norma-norma keluarga Islam ketika dilakukan dalam batas-batas yang fleksibel namun berprinsip. Sebaliknya, kesejahteraan keluarga yang optimal muncul ketika negosiasi peran didukung oleh kerja sama pasangan, fleksibilitas kelembagaan, dan interpretasi hukum kontekstual. Studi ini berkontribusi pada wacana hukum Islam kontemporer dengan menawarkan kerangka kerja yang terukur untuk menilai keseimbangan peran gender dan dengan mengusulkan model normatif yang mendamaikan prinsip-prinsip hukum Islam dengan realitas gender yang berkembang. Ini memajukan hukum keluarga Islam melampaui dikotomi yang kaku dengan mengedepankan keadilan substantif dan maslahah kontekstual sebagai standar evaluatif pusat.